Music therapy in pediatric asthma improves pulmonary function while reducing hospitalizations. (4th May 2021) - Loewy, Joanne; Goldsmith, Cody; Deshpande, Saarang; Sun, Alec; Harris, Jennifer; van Es, Cindy; Zvi, Zvi Ben-; Dahmer, Stephen
Abstract: Objective: The aim of this study was to evaluate music therapy (MT), in conjunction with standard care, as a complementary option for asthma management in pediatric patients. Methods: 173 children were randomly assigned to one of three groups: 1) Music: a single individualized MT session along with a recorder and journal with instructions for home use; 2) Music Plus: weekly group MT sessions along with a recorder and journal for home use; or 3) Control: standard of care. Primary endpoints included pulmonary function tests (FEV1, FVC, FEF25-75, PEF), hospitalizations, ER visits, missed school days, and quality of life (Juniper). Results: Significant intergroup differences relative to Controls were observed for FEV1/FVC (Music and Music Plus, p  < 0.05) and FEF25-75 (Music Plus; p  < 0.01). Music Plus participants experienced fewer hospitalizations compared to Controls ( p  < 0.001), corresponding to 1.16 fewer hospitalizations per patient-year. Caregivers' perception of their children's QOL significantly increased in the Music ( p  = 0.011) and Music Plus ( p  < 0.001) groups compared to Controls. Conclusion: These results reflect MT's potential to favorably impact pediatric asthma management as a child-friendly, low-risk intervention. Further research is needed to substantiate the possible benefits of incorporating MT into standard treatment regimens.